Natya As a Theatre of Self Fulfilment: Exploring the Relationship Between Self and Self-Fulfilment in Western Drama and Sanskrit Literature (Journal of Advances and Scholarly Researches in Allied Education, 2012)
After analysing the history of Western Dramafrom the point of view of self and self-fulfillment this chapter shall take upthe issues of self and self-fulfilment with regard to the plays in Sanskritliterature.